TINJAUAN AL-QUR’AN DAN PRINSIP PEMBEBANAN DALAM PENENTUAN DIMENSI KESTABILAN PONDASI BANGUNAN - Sedayu, Agung (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
Foundation is a part of building construction having function continuously to support entire or all the building burden to ground. One of the factor of buildingcon truction should be supported by the sturdy foundation, and sturdy foundation depend on his compiler composition and dimension of foundation. Therefore it is needed tire calculations of foundation so that we get well guaranted of his stability. Besides that, ground factor also have stability of structure, because the ground sustain the foundation and place where burden given by foundation. Power factor support the ground against the foundation action is highly varied, it is _depend on composition and nature of ground, information concerning energy number support of this ground can be shown passing investigation _of ground. To guarantee security in a building one of the among others is to looking for comparison between foundations and well-balanced ground. The dimension of foundation must be enough and fit with the power of ground. Detennination of building foundation is very influenced by energy support the ground. And energy support the ground depict strength of ground to accepted burden. Energy support the ground is very influenced by character, nature, type, structure, formation, and component compiler of ground, besides also usage of foundation type is also influenced by contour, ground water face and topography. Energy supportÂ the ground explained by some concept or theories, among others is Terzaghi theory and accepted encumbering principle or apply at the foundation structure. From both this concept determinable of enough and stable dimension of strength sustain a building. The foundation dimension is reckoned by the minimum or smallest measure or dimension, but have ever been optimal to sustain the burden befall it.